Analysis of Postgraduate Students’ Habits in Watching Preaching Videos: The Impact on the Development of Rhetorical Ability - Tarmini, Wini; Yanti, Prima Gusti; Rahman, Fauzi; Zabadi, Fairul (Jurnal Pendidikan Progresif, 2024)
Abstract: This study aimed to analyze the correlation between the habit of watching preaching videos on YouTube and the rhetorical skills of Indonesian Language Education students at the graduate school of Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA). A quantitative method with univariate-bivariate analysis was employed. The results showed that p-value (0.251) was bigger than alpha (0.05), hence H0 was accepted. These figures indicated that there was no significant correlation between the habit of watching preaching videos and the graduate students’ rhetorical skills. The odds ratio (OP) value of 0.381 within the range of 0.103-1.410 also suggested that the habit of watching preaching videos on YouTube had a power potential of 0-1 against rhetorical skills, which is categorized as low. The conclusion of this study is that while observing sermon videos does not directly enhance rhetorical skills, graduate students still need to focus on intensive training and continuous practice to improve their public speaking abilities because it will be beneficial to support their academic career.Keywords: preaching videos, rhetoric, graduate students.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202422